Structural Equation Modeling of Personality Traits and Job Satisfaction with the Mediating Role of Social Support During the COVID-19 Pandemic (Case Study: Educational-Therapeutic Staff of Teaching Hospitals in Tabriz) - Saberi, Nasim; Yari Haj Atalou, Jahangir; Hosseinzadeh, Omid Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The present study aimed to model the structural equation relationships between personality traits and job satisfaction, with the mediating role of social support among the educational-therapeutic staff of teaching hospitals in Tabriz.Methodology: This study was a descriptive-correlational research utilizing structural equation modeling. The statistical population comprised 8,500 educational-therapeutic staff members of teaching hospitals in Tabriz during 2020–2021. The sampling method was cluster sampling, and the sample size, determined based on Krejcie and Morgan’s (1970) table, was 384 participants. Data were collected using the NEO Personality Inventory, the Minnesota Job Satisfaction Questionnaire, and the Perceived Social Support Scale. Data analysis was conducted using correlation coefficients and structural equation modeling.Findings: The findings indicated a significant positive relationship between personality traits and job satisfaction, as well as between social support and job satisfaction. Furthermore, the mediating role of social support in the relationship between personality traits and job satisfaction was confirmed. Accordingly, it is concluded that considering employees' personality traits can improve the work environment and enhance their job satisfaction. Additionally, the role of social support as a mediator highlights the importance of creating a supportive atmosphere in the workplace.Conclusion: Therefore, organizations should design social support programs for their employees to strengthen self-esteem and coping abilities, ultimately contributing to increased job satisfaction.